Extracellular Recognition of Oomycetes during Biotrophic Infection of Plants - Raaymakers, Tom M.; Van den Ackerveken, Guido (Frontiers in Plant Science, 2016)
Extracellular recognition of pathogens by plants constitutes an important early detection system in plant immunity. Microbe-derived molecules, also named patterns, can be recognized by pattern recognition receptors (PRRs) on the host cell membrane that trigger plant immune responses. Most knowledge on extracellular pathogen detection by plants comes from research on bacterial and fungal pathogens. For oomycetes, that comprise some of the most destructive plant pathogens, mechanisms of extracellular pattern recognition have only emerged recently. These include newly recognized patterns, e.g. cellulose-binding elicitor lectin (CBEL), necrosis and ethylene-inducing peptide 1-like proteins (NLPs), OPEL, and glycoside hydrolase 12 (GH12), as well as their receptors, e.g. the putative elicitin PRR elicitin response (ELR) and the NLP PRR receptor-like protein 23 (RLP23). Immunity can also be triggered by the release of endogenous host-derived patterns, as a result of oomycete enzymes or damage. In this review we will describe the types of patterns, both pathogen-derived exogenous and plant-derived endogenous ones, and what is known about their extracellular detection during (hemi-)biotrophic oomycete infection of plants.